The Role of Government Policies in Environmental Management - Andriansyah Andriansyah; Endang Sulastri; Evi Satispi (Research Horizon, 2021)
Humans in meeting the needs of their lives need natural resources, in the form of land, water and air, and other natural resources that are included in renewable and non-renewable natural resources. However, it must be realized that the natural resources that humans need have limitations in many ways, namely limitations regarding their availability in quantity and quality. Certain natural resources also have limitations according to space and time. The government needs to take alternative steps to determine the potential and problems in the use of natural resources. The purpose of this study is to find out how the role of the government through its policies in managing the environment. This research uses the descriptive analysis method. The results of the study indicate that the creation of a fair and firm environmental law enforcement to manage natural resources and the environment in a sustainable manner with the support of quality human resources, the expansion of the application of environmental ethics, and socio-cultural assimilation are increasingly stable.